What are the predictors and costs of nurse absenteeism at select multicenter government hospitals? A cross-sectional study - Al Ismail, Hashem; Herzallah, Nawal H.; Al-Otaibi, Sultan T. (Frontiers in Public Health, 2023)
Objectives The purposes of this study were to determine the prevalence and cost of absenteeism in nurses as well as the factors that affect absenteeism. Methods This is a cross sectional study where a self-administered questionnaire response were obtained from 442 nurses for the previous working in 4 hospitals and 3 primary health care centers in Saudi Arabia. Analyses compared those with zero absences with those with one or more absences per month. Attributable risk was calculated as the difference in the absence percentages among nurses with high-risk exposure and low risk exposure. Results The average absence of nurses is 0.62 days per month. This results in an annual loss of around 4 million. The greatest absence frequency was significantly associated with work psychosocial factors. The modifiable factors included the clarity of work responsibilities, rating of managers, work facilities, work environment, transportation difficulties, and work satisfaction. Cost-effectiveness modules for absence intervention programs were built for these factors. Conclusions This study demonstrated that nurse absenteeism is a costly issue related to work and psychosocial factors. Preventive programs to improve the quality of work life are likely to be cost effective.